2011
DOI: 10.1038/ijir.2010.34
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for phosphodiesterase type-5 inhibitors in the treatment of premature ejaculation?

Abstract: Premature ejaculation (PE) is considered to be the most common male sexual dysfunction. The realization that PE may co-exist with ED prompted the use of PDE5-i's alone or in combination with selective serotonin reuptake inhibitors (SSRIs) for treating ejaculatory disorders. Until recently, there was little evidence that PDE5-i's alone may have a role in the treatment of PE in the absence of ED, and current available treatments include only on-demand dapoxetine. However, available data indicate that there is cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Only four reviews reported independent double data extraction 36,53,135,149 (see Appendix 4). Reported search strategies varied in terms of the search dates and resources searched.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only four reviews reported independent double data extraction 36,53,135,149 (see Appendix 4). Reported search strategies varied in terms of the search dates and resources searched.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…37 Details of the review type, the databases searched and dates, included RCTs and the AMSTAR quality assessment for these reviews of effectiveness are presented in Table 26. The overall AMSTAR quality score was 2 out of 11 in three of the reviews, 134,136,137 3 out of 11 in one review 135 and 4 out of 11 in one review. 37 However, the review by Asimakopoulos et al 134 was the most comprehensive in terms of included studies.…”
Section: 120mentioning
confidence: 99%
See 3 more Smart Citations